External auditory canal cholesteatoma: analysis of the integrity of the tissue structure - Naim, Ramin; Sadick, Haneen; Schäfer, Carsten; Hörmann, Karl (International journal of molecular medicine, 2004)
Metalloproteinases have been characterised as "destroying bulldozers" in the extracellular matrix permitting normal remodelling and contributing to pathological tissue destruction. The opposing system is established by the Cadherin-beta-catenin system, which assures the integrity of the tissue. The EACC is an extremely rare disease in the field of Otolaryngology and its incidence is estimated about 1 per 1000 new otologic patients. The aim of this study is to characterise the balance between metalloproteinases and beta-catenin in EACC tissue. Twelve specimens were obtained during surgical removal of the EACC. The EACC- and AMS-specimens were immunostained with antibodies for beta-catenin, MMP-2 and MMP-9, respectively. Immunostaining for gelatinases was increased in all layers of the EACC. However, the normal auditory meatal skin presented moderate immunostaining. In the EACC specimens, the basal layers of the matrix were positive for beta-catenin. The suprabasal layers showed diminished or negative immunostaining for beta-catenin. In all layers the AMS was homogeneously positive for beta-catenin. Metalloproteinases can modulate the balance between cellular growth and apoptosis through cleavage of non-matrix, cell-surface substrates, such as the E-Cadherin-beta-catenin system. Furthermore, this balance guarantees the integrity of the tissue. Unbalanced conditions such as described in EACC, result in unregulated desquamation and accumulation of dead keratinocytes, invasive and defective growth into adjacent tissue, and loss of growth control. Generating synthetic inhibitors of metalloproteinases for therapeutic use in EACC and other defective diseases with unbalanced tissue conditions seems useful.